Abolition of exercise induced ST depression after exercise training and its recurrence after beta blockade. Issue 2 (February 1988) - Todd, I C; McGuinness, J B; Ballantyne, D
Abstract : Exercise training can improve angina. A patient whose exercise tolerance test became normal after a year on an exercise programme nevertheless had a positive exercise test when he was taking a beta blocker. These results suggest that it may be undesirable to use beta blockers in patients with angina who are on exercise programmes.